Analysis of Operational Assistance School Fund Management - Felmi D. Lntowa; Fitria Melynsyah Yusuf; Patria Usman (Newinera Publisher, 2022)
This study aims to analyze the application of the principles of the School Expenditure Management Budget Plan (RAPBS) in improving the quality of education at SMP Negeri 6 Tolangohula. This study uses 5 types of principles of financial management of BOS funds according to Ministerial Regulation No. 6 of 2021. This type of research is descriptive qualitative research. The method used in this research is observation, interview, and documentation.The results of this study are SMP Negeri 6 Tolangohula has implemented 5 principles of financial management of BOS funds properly, in accordance with technical guidelines and legislation on BOS funds, both physically and mentally. Flexibility, Effectiveness, Efficient, Accountability, and Transparency.